SP3, a reliable alternative to HercepTest in determining HER-2/neu status in breast cancer patients. Issue 5 (5th February 2013) - D'Alfonso, Timothy Michael; Liu, Yi-Fang; Chen, Zhengming; Chen, Ying-Bei; Cimino-Mathews, Ashley; Shin, Sandra Jean
Abstract : Accurate assessment of HER-2/ neu gene status in breast cancer patients has important prognostic and therapeutic implications. Overexpression/gene amplification of HER-2 is associated with a more aggressive clinical course and eligibility for targeted therapy with trastuzumab. A variety of immunohistochemical (IHC) antibodies and in situ hybridisation (ISH) methods have been employed to assess HER-2 status. SP3 is a rabbit monoclonal antibody that has been shown to have a high level of agreement with other anti-HER-2 antibodies and ISH methods. We assessed HER-2 status by SP3 and HercepTest IHC stains and by fluorescence in situ hybridisation (FISH) on invasive breast carcinomas from paired needle core biopsy and excisional biopsy specimens from 100 patients. We compared the two antibodies with respect to concordance rates with FISH, concordance rates between samples of the same tumour, and sensitivity and specificity using FISH as the reference test. Concordance between SP3 and FISH in needle core biopsy and excisional biopsy specimens was 96% (95% CI 91.9% to 99.7%) (κ=0.89 (95% CI 0.73 to 1.00)) and 97% (95% CI 90.3% to 99.3%) (κ=0.84 (95% CI 0.66 to 1.00)), respectively. Sensitivity and specificity of SP3 for detecting HER-2 overexpression/gene amplification were 78.3% and 100%, respectively, in needle core biopsy and excisional biopsy specimens. Concordance between SP3 results assessed on the needle core biopsy and excisional biopsy was 89% (95% CI 81.2% to 94.4%) (κ=0.62 (95% CI 0.42 to 0.82)). Concordance between SP3 and HercepTest antibodies, after excluding 2+ cases, was 97.6% (95% CI 94.0% to 99.3%) (κ=0.88 (95% CI 0.77 to 1.00)). SP3 is a reliable alternative to HercepTest in evaluating HER-2 status in breast cancer patients. Like other anti-HER-2 antibodies, SP3 may serve as a diagnostic tool in breast pathology and has potential utility as an IHC biomarker in non-mammary malignancies.